Vous êtes sur la page 1sur 4

F(x)=X^3-X+2

F´(x)=3X^2-1
K Xk=g(xk-1) lf(xk)l EA=lXk-Xk-1l
1 -1.5344262295 0.0783248642 0.13442623
2 -1.521508564 0.0007659756 0.01291767
3 -1.5213797196 7.577302608E-08 0.00012884
4 -1.5213797068 0 1.2748E-08
5 -1.5213797068 0 0

F(X)=senX+Cos(x^2+1)-1 K Xk=g(xk-1) lf(xk)l EA=lXk-Xk-1l


xo=2.5 1 0
f´(x)=cosX-sen(2x) 2
3
4
5
6
7
8
9
10
11
k ak bk f(ak) f(bk) ck f(ck)
1 0 1 -1 2 0.33333333 -0.5925926
2 0.33333333 1 -0.5925926 2 0.48571429 -0.2851079
3 1 2
4 1 2
5 1 2
6 1 2
7 1 2
8 1 2
9 1 2
10 1 2
11 1 2
12 1 2
f(x)=2x^3+x-1(0,1)
f(ak)*f(ck) Ea
0.59259259
0.16895281
junior canchila monterroza
mario contreras contreras
andres sequeda martinez